PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KUALITAS SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA APARAT PEMERINTAH DAERAH - S, Samuel Parningotan; Nasir, Azwir; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to examine the effect of budgetary participation participation, human resource quality, organizational commitment and organizational culture on performance of local government apparatus. The population used in this study is government apparatus that is under the auspices of Dumai City Government is the Department. Agency, and Office of Dumai City Government.Population is a generalization area consisting of objects / subjects that have certain qualities and characteristics set by the researchers to be studied and then drawn conclusions. The sample selection was based on non-random sampling method ie purposive sampling with judgment sampling type. Due to the unavailability of the number of study population, the authors determined the criteria of respondents in this study were the heads of related institutions, treasurers, planning kasubag, and cash heads in 25 SKPD in Dumai City Government, so the amount of samples taken in this study amounted to 100 respondents. The results of the study found that: 1) Budget Participation Participation had an effect on the performance of Government Apparatus. 2) The quality of Human Resources Affects the Performance of Government Officials. 3) Organizational Commitment Affects the Performance of Government Officials. 4) Organizational Culture Affects the Performance of Government Officials.The percentage of influence of participation in budgeting, human resource quality, organizational commitment and organizational culture on the performance of local government apparatus is 61.1%Keywords :Budgetary Participation, Human Resource Quality, Organizational Commitment, Organizational Culture and Performance of Government Apparatus.